Design and simple synthesis of composite Bi12TiO20/Bi4Ti3O12 with a good photocatalytic quantum efficiency and high production of photo-generated hydroxyl radicals. Issue 38 (14th September 2016) - Du, Chun; Li, Donghai; He, Qinyu; Liu, Junming; Li, Wei; He, Guannan; Wang, Yinzhen
Abstract : Hybrid Bi12 TiO20 /Bi4 Ti3 O12 composites with a good photocatalytic quantum efficiency explained using a Z-scheme mechanism. Abstract : Hybrid Bi12 TiO20 /Bi4 Ti3 O12 composites with different Bi : Ti molar ratios were successfully fabricated using a one-step solid-state calcination. These samples were characterized using X-ray diffraction, specific surface area analysis, scanning electron microscopy, high-resolution microscopy, selected-area electron diffraction, X-ray photoelectron spectroscopy, UV-vis diffuse reflection spectroscopy, photoluminescence analyses, and photocurrent and electrochemical impedance spectroscopy. Some specified techniques were also used to investigate the photocatalytic properties and the formation of radical species under UV-vis irradiation. The composites provide an efficient pathway for photo-produced electrons and holes to diffuse and transfer to the exterior of the particles for photodegradation, because of the good contact between hybrid Bi12 TiO20 and Bi4 Ti3 O12 . Therefore, the hybrid Bi12 TiO20 /Bi4 Ti3 O12 can prolong the carrier lifetime as compared to any individual material (Bi12 TiO20 or Bi4 Ti3 O12 ). In particular, the hybrid Bi12 TiO20 /Bi4 Ti3 O12 composite with a Bi : Ti ratio of 12 : 6 had the longest photo-generated carrier lifetime and produced the maximum amount of hydroxyl radicals during UV-vis irradiation; therefore, it demonstrated the best photo-catalytic properties. A Z-scheme mechanism was proposed to explain the hydroxyl radical yield and photodegradation.